KANDUNGAN UNSUR HARA MAKRO PADA KOMPOS FIBER DAN TANDAN KOSONG KELAPA SAWIT (Elaeis guineensis Jacq.) - Herry Iswahyudi; M. Didi Iskandar (Universitas Lambung Mangkurat, 2023)
This research on Observing the content of macro nutrients in OPEFB and Fiber compost aims to determine the levels of macro nutrients N, P, K, and C-Organic contained in the compost produced in this have a look at. The composting process used EM4 material and AC water to be a mixture of ingredients in composting. EFB and Fiber composted in this composting process were 2 Kg each. This composting process lasted for 31 days. After the compost was riped, the tests for the nutrient content of N, P, K, C-Organic, and C/N ratio were conducted in the laboratory. The results of the laboratory tests on OPEFB and Fiber with indicators of N, P, K, C-Organic and C/Nratio showed that there was a variation in yield between EFB compost and Fiber compost. It showed that the different of macronutrient content of OPEFB had a N value of 2.29%, P 0.18%, K 1.54%, C- Organic 41.83%, and a C/N ratio of 17.9. Fiber compost content has a value of N 1.47%, P 0.12%, K 2.04%, C-Organic 51.13%, and a C/N ratio of 34.8. The results of the laboratory tests showed that the OPEFB compost made in this research has complied with the requirements of SNI compost 19-7030-2004.